Life science professional responsibility in an age of dual-use research - NOVOSSIOLOVA, Tatiana; PERKINS, Dana (One Health & Risk Management, 2020)
Biotechnology is progressing at an unprecedented pace promising to bring tremendous benefits by responding to health, socio-economic, and environmental challenges. At the same time, cutting-edge life science advances raise multifaceted social, legal, ethical, and security concerns, including the risk of accidental or deliberate misuse. Reconciling the expected benefits with potential risks requires effective governance of dual-use life science research. The US National Science Advisory Board for Biosecurity (NSABB), a consultative committee to the US Government defines ‘dual-use research’ as “the development of new technologies and the generation of information with the potential for benevolent and malevolent purposes” noting that “virtually all life sciences research has dual use potential”. Dual-use risk management needs to be multi-layered and flexible; regulation per se is not sufficient to capture the wide-ranging implications of cutting-edge life science advances. Fostering a shared understanding within the life science community of the risk that the life sciences could be misused in ways that cause harm to humans, animals, or plants is key. Life science stakeholders have a duty to be aware of the potential for misuse of scientific findings and of their obligation to help inform and shape critical policy decisions about biological security in the life sciences.